2013
DOI: 10.1177/1758998313479874
|View full text |Cite
|
Sign up to set email alerts
|

Grip and pinch strength: Normative data for healthy Indian adults

Abstract: Introduction Normative values of grip and pinch strength are used to determine the effect of treatment, to assess patients’ initial limitation and provide a baseline for re-assessment of patient progress. Data gathered from western populations cannot be used for reference in Indian populations due to variations in genetic, environmental and nutritional factors. Methods A convenience sample of 1005 healthy adults was recruited for this descriptive study. Grip and pinch strength were measured with elbow positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 16 publications
(21 reference statements)
2
30
0
1
Order By: Relevance
“…This finding is similar to previous studies on pinch and grip strength in both children and adults. 30,31 Dianat et al 32 compared 4 types of pinch strength between males and females between 7 and 30 years and found that males showed significantly higher strength compared with females in both the dominant and nondominant sides on all 4 strength tests. McQuiddy et al 30 also found that sex is a factor influencing grip and pinch strength in children and adolescents between 6 and 19 years.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to previous studies on pinch and grip strength in both children and adults. 30,31 Dianat et al 32 compared 4 types of pinch strength between males and females between 7 and 30 years and found that males showed significantly higher strength compared with females in both the dominant and nondominant sides on all 4 strength tests. McQuiddy et al 30 also found that sex is a factor influencing grip and pinch strength in children and adolescents between 6 and 19 years.…”
Section: Discussionmentioning
confidence: 99%
“…In this instance, the participants pinched the distal aspects of the first and second distal phalanxes, with the first digit opposing from the superior surface of the pinch point, while the second digit opposed from the inferior surface (Figure 1). Both pinch measures are frequently used to record precision manipulative strength in the medical literature (e.g., Mathiowetz et al, 1985;Mullerpatan et al, 2013). The ability of humans to produce forceful precision grips, such as the 'pad-to-side' and 'tip-to-tip' pinch, is considered unique amongst primates and is widely reported as having been essential to the use of stone tools (e.g., Marzke and Shackley, 1986;Marzke and Wullstein, 1996;Marzke, 1997;Marzke et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The HERO Grip Glove generated greater grip and pinch forces (12.7 N and 11.0 N on average) than many previous devices [12-14, 16, 43] and these forces enabled participants to grasp objects that they could not grasp otherwise. However, larger grip forces should be strived for if these forces do not sacrifice other usability criteria, since these grip forces are less than agematched norms of 294-542 N [44] and certain everyday tasks and sports activities, such as closing zippers, inserting a fork into dense food, writing with a standard pen and holding a tennis racquet, golf club or fishing rod, can require greater than 15 N of grip and pinch force [10,45]. In addition, standardized equipment and protocols are needed to evaluate the force, pressure and kinematic outputs of soft hand robots on the finger joints and skin before definitive comparisons can be made (e.g.…”
Section: Strengthening Grip Force Assistancementioning
confidence: 99%